“Zimbabwe is not a South African province”:HistoricisingSouth Africa’s Zimbabwepolicy since the 1960s (Historia, 2021)
EnglishThis paper interrogates analyses of Thabo Mbeki’s South Africa’s Zimbabwe policy which compare his approach to that of John Vorster’s government in the 1970s and decry Mbeki’s inability or unwillingness to use its ostensibly considerable hegemonic power to force Robert Mugabe to practise good governance.1 It is argued that just as Vorster used South Africa’s dominant influence over Rhodesia to “persuade” Ian Smith to negotiate with the country’s African nationalist leaders, the Mbeki administration should have taken a similar line instead of pursuing “quiet diplomacy”. The assumption is that little had changed in the relations between the two countries in the meantime and that South Africa continued to have the same level of hegemonic power over Zimbabwe. The paper argues that a more historicised approach shows that the relations between the two countries had changed so dramatically by the 1990s that South Africa no longer wielded compelling power and influence over its northern neighbour. The thirty-year liberation wars in the region and the “debt” that the ANC government owed the region for its support during the struggle, among other factors, meant that the dynamics governing South Africa–Zimbabwe relations were very different.   AfrikaansHierdie artikel bevraagteken analises wat Suid-Afrika se Zimbabwiese beleid in die Mbekiera vergelyk met dié van John Vorster se regering in die 1970’s, en wat Mbeki se onvermoë of onwilligheid betreur om sy land se oënskynlik noemenswaardige hegemoniese mag te gebruik om Robert Mugabe tot ’n verantwoordbare regering te dwing. Daar is aangevoer dat net soos wat Vorster gebruik gemaak het van Suid-Afrika se magsoorwig om Ian Smith te “oorreed” om met sy land se swart nasionalistiese leiers te onderhandel, die Mbekiregering, in plaas van sy “stille diplomasie”, dieselfde roete moes gevolg het. Die aanname is dat daar in die tussentyd weinig verander het wat betref die verhouding tussen die twee lande, en dat Suid-Afrika steeds dieselfde mate van hegemoniese mag oor Zimbabwe gehad het. Hierdie artikel voer aan dat ’n meer historistiese benadering daarop wys dat die verhouding tussen die twee lande teen die 1990’s só dramaties verander het dat SuidAfrika nie meer dieselfde mag en invloed oor sy noordelike buurman kon uitoefen nie. Die streek se dertig jaar-lange vryheidsoorloë en die ANC se “morele skuld” teenoor die streek na dié se steun tydens die vryheidstryd het, tesame met ander faktore, daarop neergekom dat die verhoudingsdinamika tussen Suid-Afrika en Zimbabwe baie anders was.
Keywords: Zimbabwe; South Africa; diplomacy; hegemony; Thabo Mbeki; Robert Mugabe; Rhodesia; sanctions; B.J. Vorster; Suid-Afrika; diplomasie; hegemonie; Rhodesië; sanksies